Fitokimia, Kadar Fenolik Total, dan Flavonoid Total serta Aktivitas Antioksidan Ekstrak n-Heksana Rimpang Temu Hitam (Curcuma aeruginosa Roxb) - Auliya Ilmiawati; Ika Resmeiliana; Ishika Jauza Nasywa; Fadia Fahira; Nafisa Muthia Wafa; M. Raffi Rayandhika; Andi Thaariq Muhammad; Arini Septianti; Hafizah Fatunisa (Jurnal Riset Kimia, 2023)
The rhizome of black turmeric (Curcuma aeruginosa) is a plant rich in benefits and has been used as a herbal medicine to treat various health problems. This study aims to obtain the n-hexane extract of black turmeric rhizome and perform phytochemical tests, determine total phenolic and total flavonoid levels, as well antioxidant tests using the DPPH method. Extraction of n-hexane from black turmeric rhizome obtained yield of 4.88%, total phenolic content of 3.01 mg QE/g extract and total flavonoids of 6.31 mg QE/g extract. The phytochemical test obtained positive results for the presence of alkaloids and flavonoids; negative tannins, steroids/triterpenoids and saponins. Antioxidant tests using the DPPH method obtained the percentage of DPPH capture ranging from 76-78%, with the largest percentage value obtained when the extract concentration was 125 ppm, which was 78.02%. This shows that black turmeric n-hexane extract has weak antioxidant activity.